2022
DOI: 10.3390/medicina58081041
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Trifecta Achievement after Percutaneous Cryoablation of Small Renal Masses: Results from a Multi-Institutional Collaboration

Abstract: Background and Objectives: To assess efficacy and safety of Percutaneous Cryoablation (PCA) of small renal masses (SRMs) using Trifecta outcomes in a large cohort of patients who were not eligible for surgery. Materials and methods: All PCAs performed in four different centers between September 2009 and September 2019 were retrospectively evaluated. Patients were divided in two different groups depending on masses dimensional criteria: Group-A: diameter ≤ 25 mm and Group-B: diameter > 25 mm. Complications r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Recent studies, such as [58][59][60][61], favored the percutaneous cryoablation over the partial nephrectomy in RCC stage cT1, especially for older people with low physical and role functional ratings and those who cannot undergo a surgical procedure. As well, [59,[61][62][63] demonstrated the role of cryoablation in reducing complications and mortality, improving the oncological results and renal function after surgery, especially in the case of endophytic renal masses [62]. Furthermore, ref.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies, such as [58][59][60][61], favored the percutaneous cryoablation over the partial nephrectomy in RCC stage cT1, especially for older people with low physical and role functional ratings and those who cannot undergo a surgical procedure. As well, [59,[61][62][63] demonstrated the role of cryoablation in reducing complications and mortality, improving the oncological results and renal function after surgery, especially in the case of endophytic renal masses [62]. Furthermore, ref.…”
Section: Discussionmentioning
confidence: 95%
“…Among the study’s limitations, we recall a need for more information on surgical schedule delays and even on survival, considering the short follow-up time. Information on specific treatments, such as cryoablation, could help in evaluating the impact of COVID-19 on surgery, as highlighted in a recent Italian work [ 49 ]. However, we could not address the issue since no cryoablation treatments were carried out in our province.…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight the relevance of the careful employment of these surgical treatments [45]. However, according to Andrea Piasentin et al [46], percutaneous cryoablation (PCA) can cause killing tumoral cells together with preserving renal function and reducing procedural-related morbidity (the so-called "Trifecta"). In this multi-institutional series, they found that PCA is more likely to achieve good outcomes measured by Trifecta in masses < 2.5 cm than in the bigger one.…”
Section: Discussionmentioning
confidence: 99%